Reasoning and its impact on grammatical thought - Al-Mozainy, Majid Mohammad (Journal of Arabic Language Sciences and Literature, 2023)
Reasoning is one of the most important features that distinguish Arabic grammar from other sciences, as grammar rules are based on reasoning, as well as rulings and phenomena, grammar directs the words of the Arabs with the modifications that God opens to it, and then builds its rules, and this is what the Arab mentality has won other cultures and languages. This study is based on the statement of the extent of the impact of reasoning on grammatical rules, and morphological, has made it in a preface in which I showed the definition of the cause, and reasoning, language and idiomatically, then the first section, and showed the effects of positive reasoning through the say supporters, then the second section and showed the effects of negative reasoning through the statements of opponents, and then concluded the research with a conclusion.